(3QSGdI aj SDGd hQO aj bhdg Udi Gddg Ydjg hSde aj OYGA GdbfhJ hdG jYR ef YGOjJs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3GdMeO ddg hcai hSdGe Ydi YHGOg GdPjf EUWai hQO Ydi SDGd ai bhdg Udi Gddg YdjI hSde ai OYGA GdbfhJ hdG jYR ef YGOjJ hPcQ GdSGFd Cfg bQCg HcSQ GdYjf s
(3BNQgG (B:s
(3hbd EPG cfJ ai PcQ GdbfhJ hdG jYR jG QH ef YGOjJ ecShQkG hGTcQ dCgd Ydhe GdTQY EP TQMhG dc GdUhGH hGHOhG ajg JPcjQkG JeJ HMeO Gddg hYhfg hMSf Jhajbg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B4s
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3GdChbGa GdYGeI (B_ (3HZOGO (B(5622) s
Keywords: (3GdeLGejYs